Efeitos da idade no comportamento das fêmeas de muriqui (Brachyteles Hypoxanthus) - Souza, Vagner de (2007)
Factors such as reproductive condition, social structure and age can influence the behavior of adult female primates. The aim of this study was to evaluate if behavioral differences inadult female northernmuriquis(Brachyteles hypoxanthus)correspond todifferences in the females’ages. Systematic behavioral data collected over a 12 month study of one muriqui group at the RPPN Feliciano Miguel Abdala, in Caratinga, Minas Gerais revealedthat young females spent significantly less timeresting, and more time feeding and drinkingwater than older females. Spatial relationships also differed by age, with older femalesspendingmoretime in contactwithadult malesand youngerfemalesspending more time within a five meter radiusofimmature males. At least some of thedifferences,such asin timespent resting and in proximity to adult males, may reflectthegreaterreproductive activityof older femalescompared to the younger females during this study